A SYSTEMATIC APPROACH IN MANAGING POST-DEPLOYMENT SYSTEM CHANGES. - Kang, David; Chiang, Roger (Communications of the ACM, 2006)
The article discusses the importance of managing computer system changes that are made post-system deployment in a systematic manner. The authors feel that more research is needed in the area of managing post-system deployment because the majority of Information Technology (IT) research has focused on managing system development. They recognize that computer system changes are often necessary after system development and deployment. However, if these changes are not made carefully, with the cooperation and feedback of users, the risks are greater than in the system development phase.